THORACIC SURGERYThe implementation of a digital chest drainage system significantly reduces complication rates after lobectomy – a randomized clinical trial - Marjański, Tomasz; Sternau, Adam; Rzyman, Witold (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Aim of the study: The aim of the study was to evaluate the impact of implementing a digital chest drainage device with regulated suction during postoperative care following a pulmonary lobectomy. Material and methods : Sixty-four patients who underwent a lobectomy at the Department of Thoracic Surgery of the Medical University of Gdańsk between June 2011 and January 2012 were included in this study. The patients were randomly divided into two groups. During the postoperative period, the patients in the study group received thoracic drainage using digital chest drainage or a conventional glass bottle. The drain was withdrawn when the daily volume did not exceed 350 ml and there was no air leakage for at least 6 hours. Results: The patients from the study and the control groups did not significantly differ with regard to the following parameters: mean age, physiological test results, presence of concomitant diseases, and surgical access to the chest. During the postoperative period, no significant differences in the drainage duration were found (Thopaz: 4 days, controls: 4 days, p = 0.919). Similarly, the period of hospitalization did not differ significantly. The general complication rate was 37%, with common complications including: atrial fibrillation (19%), atelectasis requiring bronchial aspiration (9%), and prolonged air leak (8%). The complication rate in the Thopaz group was significantly lower (25%) than in the control group (50%) (p = 0.039). There was no mortality in either group during the postoperative period. Conclusions: Withdrawing the drainage device at the daily volume of 350 ml together with the implementation of a light and compact digital chest drainage kit significantly reduces the complication rates after lobectomy.